Botswana : 2005 Article IV Consultation-Staff Report; Staff Supplement; Public Information Notice on the Executive Board Discussion; and Statements by the Authorities of Botswana. (IMF Staff Country Reports; Country Report, 2006)
The staff report for the 2005 Article IV Consultation on Botswana highlights key issues, recent developments, and policy discussions. The authorities are strengthening their structural reform agenda and moving ahead with sector-specific development programs with a view to sustaining annual growth in the 5-6 percent range as targeted in their current medium-term development plan. The authorities recognized the importance of fiscal adjustment to maintaining macroeconomic stability. They have no plans to move away from the exchange rate peg in the near term, but are exploring their options with regard to the monetary policy framework.